Financial technology adoption among small and medium enterprises in Ghana - Redeemer Krah; Lexis Alexander Tetteh; Ampaw Boateng; Richard Fosu Amankwa (Cogent Business & Management, 2024)
This study investigates the determinants of FinTech adoption among small and medium enterprises (SMEs) in Ghana, utilizing the Technology Acceptance Model (TAM) as a theoretical framework. It employed a survey design with a quantitative approach to data analysis. Data was gathered from a sample of 309 SMEs by adapting a closed-ended questionnaire. To test the hypotheses, the data were analysed using structural equation modelling Partial Least Square. The findings of this research demonstrate that the majority of the constructs in the conceptual framework has significant explanatory power in relation to the desire to embrace FinTech in Ghana. Specifically, 11 out of the total 13 hypotheses were confirmed. The key factor that positively impacts the uptake of FinTech innovations is the perceived usefulness, followed by the intention to use as the second influential factor. The results also indicate that there is a positive association between perceived ease of use and attitude towards use with FinTech adoption. Nevertheless, the observed direct impact of perceived ease of use on the adoption of FinTech is not statistically significant. But the impact of perceived ease of use on the adoption of FinTech is mediated by either perceived usefulness or intention to use. This research will assist FinTech service providers in designing FinTech services that take into account a wide range of SMEs' needs. FinTech services could be made more beneficial to build attitude affirmations and shape intentions. This will encourage SMEs and other users to use FinTech regularly and persuade nonusers to try it.The swift advancement of technology and the substantial user base of smartphones are revolutionising the manner in which the general public accesses financial services. Fintech firms continually engage in innovative practices to provide tailored products and services for individuals and small and medium-sized enterprises (SMEs), with the aim of enhancing financial accessibility and inclusivity. This is done in order to contribute towards the United Nations' goal of achieving financial inclusion as part of the Sustainable Development Goals (SDGs) by the year 2030. Fintech enables SMEs to achieve greater financial inclusion by providing them with access to digital financial solutions. The purpose of this technological breakthrough is to convert payment processes into digital formats, which would lead to decreased costs and the establishment of transparent and efficient payment systems, specifically benefiting SMEs. This study examines the factors that impact SMEs in their decision to adopt FinTech innovation for their business.
Keywords: 650; Perceived usefulness; perceived ease of use; attitude towards use; intention to use; FinTech adoption; TAM